Interrogating Households in Anticipation of Disasters: The Feminization of Preparedness - Chika Watanabe; Celie Hanson (Critical Disaster Studies, 2023)
It is now a maxim among scholars and policy-makers alike that disaster preparedness needs to involve community-based approaches in order to be effective. These include preparedness strategies in the household. But how do disaster preparedness policies and public discourses define “the household” in the first place? In this article, we explore how particular gendered notions of the household are reproduced in disaster preparedness policies and activities in Japan and the UK. Drawing on historical and cross-cultural analyses, we suggest that household preparedness efforts place the burden of labor on people coded as women—a phenomenon we call “the feminization of preparedness.” Ultimately, we suggest that when disaster policies discuss “the household,” even if they do not explicitly mention gender, there might be a problematic responsibilization of preparedness on women. Calls for the inclusion of marginalized people into disaster preparedness efforts should also be aware of the possibility of overburdening one group over others.
Keywords: Prepareadness; household; gender; feminization; Japan; UK